Efeito protetor de fitoterápicos diante da nefrotoxicidade Induzida por gentamicina em modelos animais: uma revisão da literatura - Ge, Aleff Jefferson Paiva (Universidade Federal Rural do Semi-Árido, 2020)
Herbal medicine is characterized by the medicinal use of plants or their parts. The empirical use of medicinal plants is an ancient practice and is linked to the history and culture of different populations. In Brazil, there are national policies that regulate and encourage the practice of herbal medicine. Several experiments involving herbal medicines target nephroprotective activity to prevent or treat drug-induced kidney damage. Among these drugs is gentamicin, which is an aminoglycoside antibiotic that is widely used in medical practice. In this review, a survey of 27 articles was carried out, where 26 different medicinal plants were tested in animal models of gentamicin-induced kidney damage. Of the herbal medicines analyzed, 11 are derived from plants found in national soil. The databases used to survey the studies were PUBMED, SCIELO and LILACS. The experiments showed a significant improvement in markers of renal function and oxidative stress in animals treated with medicinal plant extracts.
Keywords: Doenças do trato urinário; Plantas medicinais; Fitoterapia; Nefrotoxicidade; CIENCIAS DA SAUDE::MEDICINA